Pengaruh Kompetensi Pegawai dan Fasilitas Kerja terhadap Kualitas Pelayanan di Lingkungan Dinas Sosial Provinsi Kalimantan Timur - Rizky Nur Cahyadi; Mursidah Nurfadillah; Fenty Fauziah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of employee competence and work facilities on service quality within the Social Affairs Office of East Kalimantan Province. A quantitative research approach was employed, using questionnaires distributed to all 50 employees as the total population. Data were analyzed using multiple linear regression along with classical assumption tests to ensure the validity of the model. The results show that both employee competence and work facilities have a positive and significant effect on service quality, both partially and simultaneously. The coefficient of determination (R²) is 0.452, indicating that 45.2% of the variation in service quality can be explained by these two independent variables. Notably, work facilities exert a stronger influence (β = 0.285) compared to employee competence (β = 0.164). These findings highlight the importance of balancing employee competence development and the improvement of work facilities to ensure more effective, efficient, and responsive public service delivery.